Prospecting and Structural Insight into the Binding of Novel Plant-Derived Molecules of Leea indica as Inhibitors of BACE1 - Hosen, S.M. Z.; Rubayed, Maruf; Dash, Raju; Junaid, Md.; Mitra, Sarmistha; Alam, Muhammad Shaiful; Dey, Rupantar (Current Pharmaceutical Design, 2018)
Background: Alzheimer disease (AD) can be considered as the most common age related neurodegenerative disorder and also an important cause of death in elderly patients. A number of studies showed the correlation of this disease pathology with BACE1 inhibitor and it is also evident that BACE1 inhibitor can function as a very potent strategy in treating AD. Methods: In this present study, we aimed to prospect for novel plant-derived BACE1 inhibitors from Leea indica and to realise structural basis of their interactions and mechanisms using combined molecular docking and molecular dynamics based approaches. An extensive library of Leea indica plant derived molecule was compiled and computationally screened for inhibitory action against BACE1 by using virtual screening approaches. Furthermore, induced fit docking and classical molecular dynamics along with steered molecular dynamics simulations were employed to get insight of the binding mechanisms. Results: Two triterpenoids, ursolic acid and lupeol were identified through virtual screening; wherein, lupeol showed better binding free energy in MM/GBSA, MM/PBSA and MM/GBVI approaches. Furthermore classical and steered dynamics revealed the favourable hydrophobic interactions between the lupeol and the residues of flap or catalytic dyadof BACE1; however, ursolic acid showed disfavorable interactions with the BACE1. Conclusion: This study therefore unveiled the potent BACE1 inhibitor from a manually curated dataset of Leea indica molecules, which may provide a novel dimension of designing novel BACE1 inhibitors for AD therapy.
Keywords: triterpenoids